Role of Nursing and Emergency Medical Services in Improving Quality of Care in Tertiary Hospitals: A Review (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The emergency department within a tertiary hospital has an essential role in providing timely and life-saving health care for individuals experiencing acute and life-threatening health issues. Nurses and Emergency Medical Services (EMS) providers are the main contributors to this continuum of care by being involved with patient assessment, providing stabilization, coordinating care and taking part in quality improvement initiatives. This review itinerary explores the role of nursing and Emergency Medical Services in enhancing quality of care in tertiary-level hospitals, specifically within emergency care settings. A general, descriptive, and qualitative review of the existing literature was done using several major electronic databases, including PubMed, MEDLINE, LILACS, SciELO and the Virtual Health Library. Recent literature published from 2020 to 2025 was analyzed to develop an understanding of specific EMS and nursing practices, quality indicators and problems facing both provider groups in the delivery of care. The overall findings demonstrate that quality assessment frameworks that are structured; core competencies for nurses; nurse resiliency; and effective pre-hospital EMS systems are all critical components contributing to improved patient outcomes and service efficiency within a tertiary hospital environment. However, systemic barriers that include the lack of a sustainable workforce, burnout; limited standardized quality indicators in practice settings; and excessively stressful work environments continue to hinder the delivery of optimal patient care. This review recognizes the need for integration of nursing and Emergency Medical Services strategies that promote supportive work environments and the implementation of evidence-based quality improvement initiatives.